Polyphosphazene/Nano-Hydroxyapatite Composite Microsphere Scaffolds for Bone Tissue Engineering - Nukavarapu, Syam P. (2008)
The non-toxic, neutral degradation products of amino acid ester polyphosphazenes make them ideal candidates for in vivo orthopaedic applications. The quest for new osteocompatible materials for load bearing tissue engineering applications has led us to investigate mechanically competent amino acid ester substituted polyphosphazenes. In this study, we have synthesized three biodegradable polyphosphazenes substituted with side groups namely leucine, valine and phenylalanine ethyl esters. Of these polymers, the phenylalanine ethyl ester substituted polyphosphazene showed the highest glass transition temperature (41.6 °C) and hence was chosen as a candidate material for forming composite microspheres with 100 nm sized hydroxyapatite (nHAp). The fabricated composite microspheres were sintered into a three-dimensional (3-D) porous scaffold by adopting a dynamic solvent sintering approach. The composite microsphere scaffolds showed compressive moduli of 46–81 MPa with mean pore diameters in the range of 86–145 µm. The three-dimensional polyphosphazene-nHAp composite microsphere scaffolds showed good osteoblast cell adhesion, proliferation and alkaline phosphatase expression, and are potential suitors for bone tissue engineering applications.